ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN PADA BADAN RUMAH SAKIT UMUM DAERAH (BRSUD) TABANAN - Indrawati, Ni Made; Intan Saputra Rini, I Gusti Ayu (KRISNA: Kumpulan Riset Akuntansi, 2018)
AbstractThis research entitled "Analysis of Application of Environmental Accounting at Badan Umum Umum Daerah (BRSUD) Tabanan". This study aims to determine the application of environmental accounting at the Regional General Hospital Board (BRSUD) Tabanan as an effort to reduce the environmental impact caused byhospital operational activities and to know the reporting of environmental costs in the financial statements ofthe hospital. This research is qualitative descriptive research. The variables used in this research are environmental activity and environmental cost treatment. The result of this research is environmental activity done byBadan Badan Umum Umum Daerah (BRSUD) Tabanan that is solid and liquid waste processing by using incinerator and WWTP. Badan General Hospital District (BRSUD) Tabanan not yet apply environmental accounting perfectly according to existing theory. The Tabanan Regional Hospital Board (BRSUD) identifies theenvironmental costs as direct expenditure and indirect expenditure, recognizes the environmental costs when ithas benefited from it even though cash has not yet been issued, the measurement of environmental costs withrupiah monetary units referring to the realization of the previous period costs by the amount of costs incurred,presenting and disclosing the overall environmental costs in the financial statements together with similarcosts such as service fees and general and administrative costs. The cost of environmental quality issued by theRegional General Hospital Board (BRSUD) Tabanan amounted to 28.21% of operational cost and budgetmanagement has reached 76.62%.Keywords: Environmental accounting, environmental activities, and environmental costs